How AI can increase resilience in small and medium-sized companies - Immo Brüggemann; Stephan Buse; Nohemi Villarreal (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2025)
This paper examines how generative artificial intelligence (AI) can be integrated into the strategic management process to strengthen the resilience of small and medium-sized enterprises (SMEs). The strategic management process is divided into three phases: First, the collection and structuring of unstructured data from the macro- and microeconomic environment takes place. Here, AI provides support by efficiently collecting and clustering relevant information, enabling decision-makers to better assess current trends and developments. In the second phase, the evaluation of internal resources, AI helps to capture implicit knowledge within the company and systematically analyze it in order to uncover strengths and weaknesses. In the final phase of strategy development, AI combines internal and external data, generates new strategic approaches and thus supports the derivation of concrete fields of action. AI acts as a partner that significantly improves decision-making and strengthens the company's resilience through sound strategic planning.
Keywords: 650